Pemanfaatan Teknologi Komputer di UPU Perpustakaan Universitas Gadjah Mada = The use of the computer technology at The Main Library of Gadjah Mada University - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak.Ilmu Sosial dan Ilmu Politik UGM, 2006)
ABSTRACT The quality of the library will impact the quality of the students and the research. Main Libraty of Gadjah Mada University as a unit of the information service is expected to he able to provide the infiffnration which can the user needs. and also can be a place to process information retrieval. In addition, the available of the computer technology service can motivate the user to visit library nu-e often. Research method which is used is mixture rese.arch Le descriptive qualification and survey. The re.sprm dews vhoare interviewed cons isted ofSO. S I . 5?, S3, lecturer researcher steolUGM and the users outside of LIGM. WheiV0.5. some methods which are used were observation, interviewed and distributed the questionnaire to 200 users. Analysis is done after interpreting the result of interriews and the survey which the data Itnalysis and the process of the data collecting were observed at the same time. The 3 flow models of Miles and Thrherman in Bungin is used i,e data reduction, data presentation, and verijication. Tire result of the research ofthe computer technology use in Gadjah Mada Library. as fidlows: ii provides positive impact to the riser In visit the library, it shows 94% of the user search the rekrence materials which are used liv the lecturer including papers, lecturing materials, thesis, result of the roseatrh and result of the laboralmy it is expected the implementation of the computer technology in the library can change the catalog card to cut the long queue, it shows 75% of the user know very well horn to use the computer optimally. The user always JOIlo w the technological tread of the computer and have the enthusiasm high to read Collection of The Main Library' of Gadjah Mada University in the realitrshows 75% ha yeltd filled the user requirement, ands° do sum up the adequate computer enough, but require ro be added its amount. The service ofaccess interne! in this research is inclusive of quickly Ciiul better compared depend to library of faculty. The user used the SOUS pmgram very easy. because its program is easy to use The staff giving services attitude of the user vervAlfillecl and the system of Serl'keS circulation use one card system. .co thatftecilitate made easy staff and the user